2015
DOI: 10.1039/c5cp04084a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and excited state dynamics in a dicyanovinyl-substituted oligothiophene on Au(111)

Abstract: Dicyanovinyl (DCV)-substituted oligothiophenes are promising donor materials in vacuum-processed small-molecule organic solar cells. Here, we studied the structural and the electronic properties of DCV-dimethyl-pentathiophene (DCV5T-Me2) adsorbed on Au(111) from submonolayer to multilayer coverages. Using a multi-technique experimental approach (low-temperature scanning tunneling microscopy/spectroscopy (STM/STS), atomic force microscopy (AFM), and two-photon photoemission (2PPE) spectroscopy), we determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 56 publications
3
64
0
Order By: Relevance
“…6, we summarize the level alignments with respect to the vacuum level (E vac ). As discussed previously [28,29,50], one has to consider that electronic states determined by STS are transport states because electron tunneling into unoccupied molecular states results in the formation of negative ion resonances. On the other hand, tunneling out of occupied molecular states leads to the creation of positive ion resonances.…”
Section: Resultsmentioning
confidence: 99%
“…6, we summarize the level alignments with respect to the vacuum level (E vac ). As discussed previously [28,29,50], one has to consider that electronic states determined by STS are transport states because electron tunneling into unoccupied molecular states results in the formation of negative ion resonances. On the other hand, tunneling out of occupied molecular states leads to the creation of positive ion resonances.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been widely utilized to identify and characterize the structural and electronic details of individual molecules, including their conformation, adsorption geometry, bond order, and charge distribution . Although noncovalent bonds cannot be directly resolved in AFM images, several studies have demonstrated that the bonding structure can be precisely determined from the atomically resolved molecular arrangement . However, a detailed study of changes in geometric structure when the molecule's environment is altered by intermolecular interactions has not been addressed with AFM experimentally until now.…”
mentioning
confidence: 99%
“…[26] Although noncovalent bonds cannot be directly resolved in AFM images, [27] several studies have demonstrated that the bonding structure can be precisely determined from the atomically resolved molecular arrangement. [28][29][30][31][32][33] However, a detailed study of changes in geometric structure when the molecule's environment is altered by intermolecular interactions has not been addressed with AFM experimentally until now.Here, we report that intermolecular interactions steer the molecules into assemblies, where intermolecular interactions Molecular recognition is a crucial driving force for molecular self-assembly. In many cases molecules arrange in the lowest energy configuration following a lock-and-key principle.…”
mentioning
confidence: 99%
See 2 more Smart Citations